Investigation of the Petrographic-Mineralogical Characteristics of Metamorphic Rocks in Center of Maidan Shahr - Nabizada, Abdul Wares; Sadat, Sayed Aziz (Journal of Natural Sciences – Kabul University, 2025)
This study examines the mineralogical and petrographic characteristics of metamorphic rocks in the central part of Maidan Shahr, Maidan Wardak Province. The primary objective was to identify the mineral composition, texture, and structure of these rocks in order to better understand their formation conditions and, based on knowledge of the area's rocks, to determine their potential uses. Therefore, this research has both scientific and economic significance. Data were collected using multiple methods, including field surveys for sample collection, documentary (literature) studies, and laboratory analyses using a polarizing optical microscope (petrographic microscope). The results indicate that the rocks of the study area have undergone intense regional metamorphism, resulting in the formation of gneiss, amphibolite, and marble. The presence of minerals such as quartz, feldspar, hornblende, and garnet is indicative of high-temperature and high-pressure conditions. The mineralogical composition of these rocks has potential application in construction projects and is suitable for use as construction materials, which can play an important role in the economic development of the region.